1970
DOI: 10.3329/bjmm.v4i1.8464
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chromogenic Agar Media for Identification of Uropathogen

Abstract: Chromogenic agar media are increasingly being used as versatile tools in early differentiation and identification of Gram positive and Gram negative isolates from clinical specimens. We have evaluated the chromogenic medium as it’s use reduces the burden of biochemical characterization and reduces the workload for identification of bacteria. This study included 400 consecutively collected midstream and/or catheter-catch urine samples obtained from patients attending the hospital out patient department (OPD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
8
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
9
8
1
1
Order By: Relevance
“…1). A similar finding was reported by Sharmin et al (15), who performed medium comparison studies on 400 urine samples and plated to BA and MAC agar, CLED agar, and a chromogenic medium. They concluded that the chromogenic medium considerably reduced workload and minimized the use of conventional identification tests.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…1). A similar finding was reported by Sharmin et al (15), who performed medium comparison studies on 400 urine samples and plated to BA and MAC agar, CLED agar, and a chromogenic medium. They concluded that the chromogenic medium considerably reduced workload and minimized the use of conventional identification tests.…”
Section: Discussionsupporting
confidence: 65%
“…Chromogenic media have been reported to be an acceptable alternative to traditional media for the isolation of urinary pathogens (1,9,10,11,12,13,14). Chromogenic media may facilitate improved sensitivity of identification of some Grampositive cocci (e.g., enterococci) in mixed cultures with Enterobacteriaceae and may promote more uniform interpretation of urine culture plates by less experienced bench technologists (1,10,13,15). Chromogenic media may also promote more rapid identification of the etiological agent(s) of infection and may provide clinicians with relevant information regarding their choice of empirical antimicrobial therapy for their patients.…”
mentioning
confidence: 99%
“…Rahman et al [31] and Ahmed and Rashid [32] in their studies in Bangladesh also reported E. coli as being the commonest pathogen responsible for bacteriuria which is consistent with the findings of this study. The findings of E. coli are also in agreement with the study done by Sharmin [33] in Bangladesh. Another study done by Hasan et al [34] in a tertiary hospital in Indian study showed 50.7% incidence of UTI caused by E. coli, which was nearer to our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings correlate with the study done by Manjusree BS and Sharmin et al 11,12 Out of 199 pure growths, 126 were gram negative bacilli and 56 were gram positive cocci and 17 were Candida species. In the present study, gram negative bacilli outnumbering gram positive cocci.…”
Section: Discussionsupporting
confidence: 81%